Morales-Ladrón, Marisol. Family and Dysfunction in Contemporary Irish Narrative and Film - Eufrausino, Caroline Moreira (ABEI Journal, 2016)
Morales-Ladrón, Marisol. Family and Dysfunction in Contemporary Irish Narrative and Film. Bern: Peter Lang, 2016.352 pp.